Intermediate Clinical and Radiographic Outcomes of the Inbone II: for Patients with Five Years Minimum Follow-up - Parin Kothari MD; Alexander Phillips; Ramsey Potter; Drew Albert MD, MBA; Michelle A. Padley PhD, CRTM; John G. Anderson MD; Donald R. Bohay MD, FACS; John D. Maskill MD; Marshall A. Boose DO; Lindsey A. Behrend BS (Foot & Ankle Orthopaedics)
Category: Ankle Arthritis; Ankle Introduction/Purpose: The TAA was originally introduced in the 1970s and each subsequent generation of implant has been improved upon. Innovative solutions led to second and third generation arthroplasties, which addressed the initial failures and incorporated new designs to improve patients’ lives through significant improvements in pain and function. The Inbone II Total Ankle System was made available in 2009. The successor to the Inbone I, it features pivotal changes to both the tibial stem and talar components. The purpose of this study is to gather intermediate (five or more year follow-up) data on the Inbone II Total Ankle Systems since it's approval in 2009. Methods: The study is retrospective, single-site cohort of patients who have undergone one or multiple surgeries involving the Inbone II Total Ankle System by the senior authors with at least 5 years of follow-up. For patients that are able to be reached, and choose to consent, a prospective clinical visit was conducted. This visit included physical and radiographic assessments, as well as patient-reported outcome measures. Results: Initially, 168 potential patients (77 females and 72 males) and were identified. The average patient was 62.5 years (range: 25 - 88) at surgery. Following retrospective data collection, these post-operative dispositions were noted: (19 (11.3%) declined prospective follow-up, 29 (15.5%) were lost to follow-up, 5 (3%) underwent amputations, 7 (4.2%) were explanted, and 2 (1.2%) expired). Of these, 59 (35%) patients (63 implants) have returned to the office for prospective assessments. Of these, 28 were female, and 31 were male. The mean time from surgery was 7.2 years (6.4 to 10.6). 15 reported complications following the procedure, most commonly noted as residual post-operative swelling (7 patients). Patient satisfaction was noted to be 93% overall, with an average AOFAS score of 84.2% (52 - 100). Conclusion: Preliminary data demonstrates that ankle replacement with the Inbone II device has the equivalent survival rate as that reported in the literature at 5 years post surgery.